(untitled) (Archives of Clinical Psychiatry, 2004)
Epilepsy, a neurological disorder, presents a high frequency of psychiatric disorders, especially depression, which is the most common psychiatric comorbidity in these patients. It's known that depressive disorder may compromise these patient's life more than the severity of epilepsy, pointing to the importance of its diagnosis. However, there are few studies on the prevalence and clinical presentation of depression in childhood and adolescence and none on its treatment. This article aims to study the reasons for the subdiagnosis of this psychiatric disorder and review the evidences for the occurrence of possible common pathogenic mechanisms. For this purpose, we reviewed studies from animal models of epilepsy showing a decreased activity of neurotransmitters, also implicated in the pathogenic mechanisms and treatment of depression. Additionally, we studied the evidences from neuroimaging and neuropsychological studies that corroborate the existence of a limbic structure dysfunction - frontal and temporal - in patients with depressive disorders, which apparently also co-exists in patients with epilepsy. Therefore, this article provides evidence that the concept of a cause- consequence relationship demands revision.